Suppression of ferroelectric phase-transition in niobates via solid solution formation - Lanfredi, S. [UNESP]; Praxedes, F. R. [UNESP]; Ivashita, F. F.; Paesano, A.; Nobre, M. A.L. [UNESP] (Elsevier, 2019)
Suppression of the phase-transition type ferro-paraelectric from doping of KSr2Nb5O15 host-structure was investigated by set of techniques X-ray diffraction, Mössbauer spectroscopy and Dielectric spectroscopy at high temperature. High crystalline and single phase iron-doped niobate ceramic with Tetragonal Tungsten Bronze TTB-type structure, stoichiometry KSr2(FeNb4)O15-δ, was prepared by conventional technique using high energy milling. Both techniques Rietveld Method and Mössbauer spectroscopy showed that Fe3+ cations occupy two different octahedral sites in the TTB structure on the niobium octahedral sites, termed as Nb(1) and Nb(2). At room temperature, the dielectric permittivity value of the KSr2(FeNb4)O15-δ is two times higher than the permittivity values of the KSr2Nb5O15. The suppression with extinction of ferro-para phase-transition occurs as function of break-down of polar characteristic. New non-polar space group development stemming from solid solution formation is discussed.
Keywords: Dielectric spectroscopy; Mössbauer spectroscopy; Niobate; Phase-transition suppression